A pharmacoeconomic analysis of sertindole in the treatment of schizophrenia - I. S. Krysanov; V. Yu. Ermakova (Качественная клиническая практика, 2018)
We conduct a comparative cost-effectiveness and budget impact analysis of atypical antipsychotics for the treatment of schizophrenia - sertindole versus quetiapine, paliperidone. The primary outcome of interest was rehospitalization rates. The cost of the annual treatment of patients with schizophrenia in the outpatient setting was calculated, costs of hospital readmission and total costs.